Physiotherapy Treatment in Cases of Weber Type a Sinistra Fractures with Infrared Modalities, Exercise Theraphy and Transcutaneus Electrical Nerve Stimulation (TENS) at Rsud Dr. H. Soemarno Sostroatmodjo Tanjung Selor - Ratu Mandalika Laaysatu Rahman; Qudus, Abdul (International Journal of Psychology and Health Science, 2025)
A weber fracture is a fracture of the fibula bone and is accompanied by severe pain and is usually swelling. This is caused by injuries such as accidents or excessive pressure and must be treated consistenly to prevent long-term consequences of the fracture (B. Harvella. RG, et al, 2024). To determine the implementation of physiotherapy to reduce pain, increase muscle tone, reduce edema and increase the range of motion joint. Using infrared physiotherapy modalities, exercise therapy and Transcutaneus Electrical Nerve Stimulation (TENS). Form the results obtained during 6 therapies, the data obtained were a decrease in silent pain from T0 : 0 to T6 : 0, motion pain from T0:5 to T6 : 3+ and tenderness from T0 : 7 to T6 : 4+. Increased strength of thr dorsal flexor and plantar flexor muscles from T0 : 4 to T6 : 4+, invertor and evertor muscles strenght from T0 : 3 to T6 : 3+. Decreased edema from the tibial tuberosity axist point to distal 10 cm from T0 : 25.5cm to T6 : 30.5 cm, tibial tuberosity to distal 15 cm from T0 : 26 cm and tibial tuberosity to distal 20 cm from T0 : 22 cm to T6 : 23 cm. And increased actived joint range of motion from T0 : S = 260 – 00 – 160, F = 300 - 00 – 100  to T6 : S = 270 – 00 – 170 , F = 310 – 00 – 110. And passive range of motion of T0 : S = 270 – 00 – 170 , F = 310 – 00 – 130  to T6:S = 280 – 00  - 180 , F = 320 – 00  - 180